Varietal Differences in Wet Damage of Broccoli (Brassica oleracea L. var. italica) Under Waterlogging Conditions - Hara Ryo; Jitsuyama Yutaka; Suzuki Takashi (Journal of Horticultural Research, 2023)
Broccoli is a typical wet-sensitive vegetable. Precipitation levels in Japan have been unusually high recently, so the wet tolerance of broccoli is of great interest to farmers. The purpose of this study is to gather basic information to help with broccoli cultivation in unusually wet conditions by investigating the varying responses of different cultivars to wet conditions. In two-year pot experiments, the early stage of broccoli growth was compared using on cultivars that exhibit unique characteristics in terms of tolerance to wet conditions, and differences in yield were also confirmed during the harvest season in a field experiment. Broccoli plants subjected to three days of waterlogging treatment exhibited wilting, yellowing and reduced biomass. Significant interactions between treatment and cultivar were also detected for biomass, water content, and photosynthetic ability. The ‘Shigemori’ cultivar showed less susceptibility to wet damage compared to the other cultivars. The trend could be observed in the head yield in the field experiment. The unique cultivars shown in this study may be helpful in broccoli cultivation and may be suitable for use as parent material in breeding. Furthermore, a short-term pot experiment can help evaluate broccoli wet tolerance during the early growth.